Faktor Risiko Campak Anak Sekolah Dasar pada Kejadian Luar Biasa di Kabupaten Pesawaran, Provinsi Lampung - Ferry Ardhiansyah; Kamilah Budhi Rahardjani; Ari Suwondo; Mexitalia Setiawati; Apoina Kartini (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
Background: Measles is a contagious disease, still a health problem in Indonesia. In 2017 the measles BIAS immunization coverage in Pesawaran District was 98.8%, although coverage was quite good, measles cases in primary school-aged children were still common until the outbreak occurred. This can be caused by various child factors, maternal factors, and environmental factors. This study wants to examine the effect of child, maternal and environment factors on the incidence of measles in primary school-aged children in measles outbreaks event in Pesawaran District.Methods: Mix methods research with case control study design supported by in-depth interviews. The participants were 81 volunteer, consist of 27 cases and 54 controls taken by purposive sampling. Dependent variable was incidence of measles in primary school age children in the outbreak event. Independent variables were child, maternal and environment factors.  Bivariate and multivariate analysis.Result: Variables that had been proven to affect incidence of measles in Pesawaran District, were history of measles immunization (p= 0,004 OR = 13,716, 95%CI = 2,286-82,301), contact history with measles case (p=0,024 OR = 4,141, 95%CI = 1,208-14,201), occupancy density (p= 0,036 OR = 3,971, 95%CI = 1,092-14,443), and home ventilation (p= 0,036 OR = 3,591, 95%CI = 1,089-11,843). The resuts of the in-depth interviews supoorted the results of quantitative analysis that there was still a clash of religious leaders who did not support immunization.Conclusion: Factor that had been proven to the incidence of measles in primary school-age children in outbreaks were the history of measles Immunization/BIAS, history of contact with measles case, occupancy density, and home ventilation strengthened by the support of religious leaders towards immunization.